Water restriction in cowpea plants [Vigna unguiculata (L.) Walp.]: Metabolic changes and tolerance induction - Alberto S. de Melo; Yuri L. Melo; Claudivan F. de Lacerda; Pedro R. A. Viégas; Rener L. de S. Ferraz; Hans R. Gheyi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Global climate change tends to intensify water unavailability, especially in semi-arid regions, directly impacting agricultural production. Cowpea is one of the crops with great socio-economic importance in the Brazilian semi-arid region, cultivated mainly under rainfed farming and considered moderately tolerant to water restriction. This species has physiological and biochemical mechanisms of adaptation to these stress factors, but there is still no clear vision of how these responses can not only allow survival, but also ensure yield advances in the field. Besides acclimation mechanisms, the exogenous application of abiotic (salicylic acid, silicon, proline, methionine, and potassium nitrate) and biotic (rhizobacteria) elicitors is promising in mitigating the effects of water restriction. The present literature review discusses the acclimation mechanisms of cowpea and some cultivation techniques, especially the application of elicitors, which can contribute to maintaining crop yield under different water scenarios. The application of elicitors is an alternative way to increase the sustainability of production in rainfed farming in semi-arid regions. However, the use of eliciting substances in cowpea still needs to be carefully explored, given the difficulties caused by genotypic and edaphoclimatic variability under field conditions.